1992
DOI: 10.1038/jcbfm.1992.13
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Brain Monoaminergic Neurotransmitter Concentrations in Rat after Intracerebroventricular Injection of Streptozotocin

Abstract: Summary:The tissue concentrations of the monoaminer gic neurotransmitters noradrenaline (NA), dopamine, and serotonin (5-HT) and of their major metabolites were measured by HPLC and electrochemical detection in sev eral rat brain areas after intracerebroventricular injection of streptozotocin (STZ). NA levels were found to be de creased in the frontal cortex by 14%, in the entorhinal cortex by 18%, and in the striatum by 38%. In the ento rhinal cortex, 5-HT levels were decreased by 19% and the 5-HT turnover ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 65 publications
(31 reference statements)
0
16
0
Order By: Relevance
“…The effect is obviously not a consequence of trauma caused by unilateral icv administration, always applied in the right lateral ventricle, because a similar increase is observed both in the striatum of the left and the right hemisphere. Recently, Ding et al (1992) found no changes of rat striatal DA content three weeks after icv administration of streptozocin. Beside a longer post treatment observation than in our experiment, however, a great age-difference (one year old rats in their and two month old ones in our experiments) between their and our experimental animals should be kept in mind.…”
Section: Discussionmentioning
confidence: 98%
“…The effect is obviously not a consequence of trauma caused by unilateral icv administration, always applied in the right lateral ventricle, because a similar increase is observed both in the striatum of the left and the right hemisphere. Recently, Ding et al (1992) found no changes of rat striatal DA content three weeks after icv administration of streptozocin. Beside a longer post treatment observation than in our experiment, however, a great age-difference (one year old rats in their and two month old ones in our experiments) between their and our experimental animals should be kept in mind.…”
Section: Discussionmentioning
confidence: 98%
“…A number of neurotransmitters (neuromodulators) and their receptors, such as glutamate and asparate, which bind to the NMDA receptor [31,[33][34][35], insulin [36][37][38][39][40][41], and others [35,[42][43][44], have been shown to be involved in normal and abnormal mental processing, either directly or indirectly [45][46][47][48][49], Modulation substances such as those mentioned above, bind specifically to cell surface receptors. They modulate the interrelation of the cell with the extracellu lar environment by excitation and inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental DM in animals is usually produced by betacytotoxic (BCT) drugs streptozotocin (STZ) and alloxan (AL) which given parentherally in high doses damage pancreatic beta cells and decrease insulin production/secretion [9]. Central, intracerebroventricular (icv) administration of low STZ and AL doses, respectively, does not produce DM in rats, but produces regionally specific brain neurochemical changes that are, in general, similar to those found in BCT-induced diabetes [10][11][12][13]. Because of induction of the long-term and progressive cognitive deficits and decreased brain glucose and energy metabolism [14,15], STZ-intracerebroventricularly (STZ-icv) treated rats have been proposed as an experimental model of sporadic Alzheimer's disease (sAD) in which the existence of the brain type of non-insulin dependent diabetes («cerebral diabetes») has been suggested [16].…”
Section: Introductionmentioning
confidence: 98%